EFEKTIVITAS KOMUNIKASI ANTARPRIBADI MAHASISWA DAN DOSEN PEMBIMBING SKRIPSI - Prininta, Nadia; Sudaryanto, Edy; Jupriono, Jupriono (representamen, 2015)
Communication between students and thesis supervisor is a form of interpersonal communication inboth directions, because the communication is done by the students with the thesis supervisor, allowingeach party either students or thesis supervisor giving each response as feedback from the message.Feedback responses can be either verbal or non-verbal language . Effective communication betweenstudents and professors pembibing thesis, is expected to be helped to overcome obstacles or problemsthat occur in the preparation of the thesis. Formulation of the problem in this research is "How can theeffectiveness of inter- personal communication students and lecturers in the process of preparation of thethesis?". This study used a qualitative descriptive method by distributing questionnaires to a samplewithdrawal . Sample in this study was the student of the Department of Social Communication August 17,1945 Surabaya University class of 2011. From this study , the authors would like to explain that byapplying interpersonal communication and equip it with the concept of the legal aspects of effectivecommunication "REACH" raised by Hardjana in Suranto, communication between students and lecturerswill be effective because it is a component of interpersonal communication that can foster one'srelationship with others of the message may give a sense of pleasure and comfort in a person .Key Words: effectiveness of communication, Department of Social Communication Untag Surabaya ,effective communication law " REACH .